CONCEPT, SCOPE, STRUCTURE OF AIR LAW AND ITS PLACE IN THE RIGHTS OF UKRAINE - Цимбалюк, В. С. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article violated problems regarding the definition, object, structure, air law and its place in the law of Ukraine.